SPECTROPHOTOMETRIC DETERMINATION OF BORON IN FOOD PRODUCTS BY ESTER BORATE DISTILLATION INTO CURCUMIN - Adu, R. E. Y.; Roto, R.; Kuncaka, A. (Jurnal Kimia (Journal of Chemistry), 2021)
Spectrophotometric determination of boron in food products by ester borate distillation into curcumin was studied. The sensitivity and selectivity of curcumin method were overcome by generating ester borate at proper temperature, time and pH. Boron was separated as triethyl borate by distillation in a vessel using ethanol solvent and reacted with curcumin. Distillation system reached optimum condition at temperature of 75 o C and pH 5-6. Boron-curcumin complex was measured at 555 nm after 10 minutes of reaction. Separation of boron by distillation method complied with validation parameters. The standard curve was linier at concentration range of 1.2-4.8 ppm (R 2 =0.9995) and had molar extinction value (?) 4.7 x 10 5 L mol -1 cm -1 for high sensitivity level which is higher than the previous study. Percent recovery was found to be 96.09-104.92 %. Boron content in meatball and tofu products was in the range of 1.406-3.589 and 0.010-1.085 mg/kg. Ester borate distillation into curcumin has been successfully applied to the determination of boron in food products because of its high selectivity and sensitivity.